Anti-endotoxin effects of terpenoids fraction from Hygrophila auriculata in lipopolysaccharide-induced septic shock in rats. (2nd April 2016) - Hussain, Md. Sarfaraj; Azam, Faizul; Ahamed, K. F. H. Nazeer; Ravichandiran, V.; Alkskas, Ismail
Abstract: Context : Hygrophila auriculata (K. Schum) Heine (Acanthaceae) has been traditionally used for the treatment of various ailments such as inflammation, rheumatism, jaundice and malaria. Objective : The present study aims to separate terpenoid fraction (TF) from alcohol (70%) extract of the whole plant of Hygrophila auriculata and assess its anti-inflammatory activity. Materials and methods : HPTLC analysis of TF was performed for the estimation of lupeol. Edema was induced in Wistar albino rats by subplanter injection of 0.1 ml of 1% (w/v) carrageenan into the right hind paw after 1 h of TF administration (100 and 200 mg/kg oral). Septic shock was induced by intraperitoneal administration of LPS (100 μg/kg) in rats and interleukins (IL-1β and IL-6), tumor necrosis factor (TNF-α), superoxide dismutase (SOD), lipid peroxidation (LPO), and nitric oxide (NO) were measured in serum. AutoDock 4.2 was used for molecular docking. Results : Administration of TF significantly ( p < 0.005) restored the serum levels of cytokines, LPO (7.77 ± 0.034 versus 4.59 ± 0.059 nmole of TBARS), NO (9.72 ± 0.18 versus 4.15 ± 0.23 µmol nitrite/mg of wet tissue), and SOD (4.89 ± 0.036 versus 7.83 ± 0.033 Unit/mg protein) compared with the LPS-challenged rats. Analysis of in silico results revealed that TNF-α is the most appropriate target in eliciting anti-inflammatory activity. Conclusion : The present findings suggest that TF of Hygrophila auriculata possesses great promise as an anti-inflammatory agent which may be due to its antioxidant effect. Molecular docking results could be exploited for lead optimization and development of suitable treatment of inflammatory disorders.